KEADAAN INSOLVENSI SEBAGAI ALASAN PEMBUBARAN PERSEROAN TERBATAS BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - , Efendy H. Purba ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study on insolvency condition as the reason of the dissolution of limited liable companyâs legal entity based upon Law Number 37 of 2004 concerning Bankruptcy and Debt Moratorium aims at 1) reviewing any applicable laws and regulations governing the dissolution of any bankrupt limited liability company whose assets are insolvent